2020
DOI: 10.1123/jsr.2018-0236
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Quadriceps Strength Recovery After Anterior Cruciate Ligament Reconstruction With Hamstring Autograft: Patients Stratified by Preoperative Quadriceps Strength Deficit

Abstract: Context: Some studies have discussed postoperative quadriceps strength recovery after anterior cruciate ligament reconstruction (ACLR). However, the effect of preoperative quadriceps strength deficit on longitudinal postoperative quadriceps strength recovery after ACLR with hamstring autograft is unknown. Objective: To reveal the longitudinal postoperative quadriceps strength recovery after ACLR with hamstring autograft among patient groups stratified by preoperative quadriceps strength deficit. Design: Retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Previous studies have reported that the preoperative LSI of IKE affects the recovery of IKE postoperatively. 47 In the future, we need to measure the data prospectively and conduct a multivariate analysis, which includes other variables to examine the impact of each variable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the preoperative LSI of IKE affects the recovery of IKE postoperatively. 47 In the future, we need to measure the data prospectively and conduct a multivariate analysis, which includes other variables to examine the impact of each variable.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we recognize that preoperative quadriceps strength correlates with postoperative quadriceps strength and single-leg hop performance. 33 Given the retrospective nature of the data, we were unable to compare preoperative strength between the sexes. Finally, we recognize the potential for sampling bias, as patients were selected from those who participated in functional testing at our injury prevention center 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the potential influence of bilateral AMI after unilateral ACLR, 14,15 the goal of restoring RFD ability to the level of the uninjured contralateral limb using a LSI may underestimate the true recovery from ACLR surgery. 56 Thus, pre-injury testing, 112 pre-surgery testing, 113,114 comparison to matched uninjured controls, 56,58,65 and/or a comparison to normative values 33 should be considered alongside a LSI when evaluating RFD and maximal strength capacity (MVC) after ACLR.…”
Section: Aclr and Intrinsic Muscular Factors Affecting Rfd Between-mentioning
confidence: 99%
“…Interestingly, high pre-operative quadriceps strength LSI (>80%) has been positively associated with accelerated quadriceps LSI recovery when compared to lower pre-operative LSI. 113 ACLR surgical procedures including the use of autograft or allograft techniques and their effect on knee extensor and flexor RFD should also be examined. Of importance is evaluating the co-morbidity effects from the use of autografts (eg, bone-patellar tendon-bone or semitendinosus autograft) compared to allografts.…”
Section: Study Limitationsmentioning
confidence: 99%